The Bullary as a New Type of Cartulary: The Example of Becerro III of San Millán de la Cogolla - Leticia Agúndez San Miguel (Studia Historica. Historia Medieval)
Following the famous miscellaneous volume of 1993 dedicated to the study of cartularies, part of the historiographical attention on these manuscripts has focused on their typological diversity. This study aims to advance research in this specific area by investigating the emergence of cartularies devoted to the preservation of papal documents. Such manuscripts have been known as bullaria (or bullaries in English and bularios in Spanish) since the early Modern Age, the period of their maximum diffusion. In the Iberian Peninsula, there survive several exemplars from the thirteenth and fourteenth centuries that can be interpreted as precursors of this new typology. Due to its early chronology, the Becerro III of the monastery of San Millán de la Cogolla is an excellent starting point for this investigation. The study of this manuscript reveals that, despite its factitious nature, the monks’ creation of a dossier of papal privileges which opens the manuscript can be recognised as a «proto-bullary», which anticipated by several centuries the definition and diffusion of a new type of cartulary.